2021
DOI: 10.3389/fchem.2021.671575
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalysis of SnO2-CNTs Composite for VO2+/VO2+ and V2+/V3+ Redox Reactions

Abstract: In this study, a SnO2-carbon nanotube (SnO2-CNT) composite as a catalyst for vanadium redox flow battery (VRFB) was prepared using a sol-gel method. The effects of this composite on the electrochemical performance of VO2+/VO2+, and on the V2+/V3+ redox reactions and VRFB performance were investigated. The SnO2-CNT composite has better catalytic activity than pure SnO2 and CNT due to the synergistic catalysis of SnO2 and the CNT. SnO2 mainly provides the catalytic active sites and the CNTs mainly provide the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…3 d, the Sn 3d main peak of 25 nm SnO 2 -CNT was fitted into 2 peaks: Sn 3d 3/2 (∼495.06 eV) and Sn 3d 5/2 (∼486.60 eV) [83] , [90] . The binding energy difference between Sn 3d 5/2 and Sn 3d 3/2 was measured to be around 8.46 eV with an area ratio of 1.46, which validated the development of tetragonal SnO 2 on CNT membranes [76] , [89] . The chemical interaction between the deposited SnO 2 and CNTs via covalent bonding may alter the surface charge and wettability of CNT-based membranes [88] , [89] , [91] .…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…3 d, the Sn 3d main peak of 25 nm SnO 2 -CNT was fitted into 2 peaks: Sn 3d 3/2 (∼495.06 eV) and Sn 3d 5/2 (∼486.60 eV) [83] , [90] . The binding energy difference between Sn 3d 5/2 and Sn 3d 3/2 was measured to be around 8.46 eV with an area ratio of 1.46, which validated the development of tetragonal SnO 2 on CNT membranes [76] , [89] . The chemical interaction between the deposited SnO 2 and CNTs via covalent bonding may alter the surface charge and wettability of CNT-based membranes [88] , [89] , [91] .…”
Section: Resultssupporting
confidence: 60%
“…In Fig. 3 c, the O 1 s main peak of 25 nm SnO 2 -CNT was deconvoluted into 3 peaks: O–C/O–H (∼531.70 eV), C O (∼532.96 eV), and O-Sn (∼530.46), demonstrating the covalent Sn–O–C bonding between SnO 2 and CNTs [88] , [89] . In Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Feng et al reported that the SnO 2 -CNT composite improves the catalytic activity of pure SnO 2 and CNTs due to the synergistic effect between these materials. The CNTs provide a three-dimensional structure and high electrical conductivity, while SnO 2 contributes to the catalytic active sites, thus improving catalyst efficiency [65]. David et al reported the production of hybrid materials based on MWCNTs and different types of NP, such as ZnO, Ag, etc., with antimicrobial properties to improve antimicrobial activity.…”
Section: Synergistic Effects In Combined Systemsmentioning
confidence: 99%
“…As mentioned above, CNTs exhibit distinct band structures attributed to chirality control, influencing light absorption and enhancing the absorption spectra. Many reports presented enhanced photocatalysis by modifying the band structure of CNTs by heteroatom doping, by forming composites or anchoring nanoparticles, producing a synergistic effect between CNTs and additional elements [64,65].…”
Section: Advances In Photocatalysis and Carbon Nanotubesmentioning
confidence: 99%
“…[8][9][10] However, these electrode materials often suffer from poor activity and so require further treatment to improve their performance and ensure the economic feasibility of RFBs as an energy storage technology. Electrode pretreatment methods such as thermal, [11][12][13][14][15][16][17][18] chemical, [19][20][21][22][23][24][25][26][27] electrochemical oxidation, [28][29][30] catalyst deposition, [31][32][33][34][35][36][37] and the use of nanomaterials [38][39][40][41][42][43][44][45] are often explored in literature, where the objective is to introduce new active sites, increase the electrochemically active surface area, and improve wettability to better facilitate the redox reactions.…”
mentioning
confidence: 99%